LOYALITAS PELANGGAN DITINJAU DARI EKUITAS MEREK PROMOSI DAN LOKASI - Agus Gunawan (ITB AAS Indonesia Surakarta, 2024)
This study)aims to prove the effect of brand equity, promotion and location on customer loyalty)in Assalaam Hypermarket Surakarta the city of Solo. The growth and development of shopping centres are increasing rapidly causing intense competition with other shopping centres. Business owners also prepare the best strategy to survive in all conditions. The best strategy can be taken by considering the opportunities that exist. Making the right and effective business decisions can be a solution to various problems being faced. Using this type of quantitative research. For this study the population is infinite. The sampling technique used)is simple random sampling, so that a sample of 100 people is taken. The)data technique collection using.interview, kuesioner and documentation. The data analysis technique used)in this study is multiple linear)regression analysis with the help of the program SPSS Statistics.The results of)path analysis showed that brand)equity, promotion and location affect the simultaneous and significant impact on customer loyalty in Assalaam Hypermarket Surakarta. T test results showed that brand equity affects customer loyalty in Assalaam Hypermarket Surakarta. Promotion affects customer loyalty in Assalaam Hypermarket Surakarta. Location affects customer loyalty in Assalaam Hypermarket Surakarta. Suggestions from this research, Assalaam Hypermarket Surakarta should maintain and improve aspects related to brand equity, promotion and location. Keywords: Brand Equity, Promotion, Location and Customer Loyalty